The effect of Using a Book Al-Qawā‘idu Aṣ-ṣarfiyyatu Fī Al-Lughah Al-‘Arabiyyah on The Results of Learning Sharaf at The Islamic Education School in Pasia (MAN Insan Cendekia Jambi, 2025)
The study conducted by Nurul Mawaddah Al-Mursal (Student ID 2220002), entitled “The effect of using a book Al-Qawā‘idu aṣ-ṣarfiyyatu fī al-lughah al-‘arabiyyah on the results of learning Sharaf at the Islamic Education School in Pasia”, investigates the impact of using the Arabic grammar book Al-Qawā‘idu aṣ-ṣarfiyyatu fī al-lughah al-‘arabiyyah on students’ learning outcomes in the subject of Sharaf. The research was motivated by the difficulties students encounter in studying Sharaf due to the complexity of the instructional materials, which in turn leads to lower academic achievement. The main objective of this study is to assess whether the use of the mentioned book can serve as an effective alternative resource to enhance student performance in Sharaf at MTI Pasia Islamic Boarding School. This research applies a quantitative approach with an experimental design, specifically a quasi-experimental model. The design involves both an experimental and a control group, with tests administered as the research instrument. Findings reveal that the application of Al-Qawā‘idu aṣ-ṣarfiyyatu fī al-lughah al-‘arabiyyah significantly improves students’ outcomes. This is evidenced by hypothesis testing results showing the calculated t-value exceeds the critical t-value at the 5% significance level (5.390 > 2.021). Consequently, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. Moreover, the effect size test yields a value of 1.28, which surpasses 0.8, indicating a strong effect. These results confirm that the use of this book substantially contributes to improving students’ learning achievements in the Sharaf subject.